Answer:
DF = 57
Step-by-step explanation:
DE + EF = DF
DE = 4x + 10
EF = 2x - 1
DF = 9x - 15
First, solve for the given equation. Plug in the corresponding terms to the corresponding variables:
DE + EF = DF
(4x + 10) + (2x - 1) = (9x - 15)
Combine like terms:
(4x + 2x) + (10 - 1) = 9x - 15
6x + 9 = 9x - 15
Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Subtract 9 & 9x from both sides:
6x (-9x) + 9 (-9) = 9x (-9x) - 15 (-9)
6x - 9x = -15 - 9
-3x = -24
Divide -3 from both sides:
(-3x)/-3 = (-24)/-3
x = -24/-3
x = 8
Plug in 8 for x in the equation given for DF:
DF = 9x - 15
DF = 9(8) - 15
Remember to follow PEMDAS. First multiply, then subtract.
DF = 9(8) - 15
DF = 72 - 15
DF = 57
DF = 57
~